The Impact of Veto Power on the Enforcement of International Law: A Case Study of the Israeli-Palestinian Conflict - Nanda Gusti Octaviansyah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The conflict between Israel and Palestine has been an international attention and has become one of the most complicated issues in the international politics. Veto power exercised by one of the five permanent members of the United Nations Security Council has been an element influencing the obstruction of resolutions addressing this conflict and international law violations. The concept of veto has allowed the permanent member, particularly the United States, to prioritize its political interest over international peace and security. This article explores the role of the veto power within the United Nations Security Council in obstructing the enforcement of international law, specifically in the context of conflict between Israel and Palestine. This article also discusses on how the United States has consistently exercise its veto to block any resolution that supports Palestine, aggravating the situation of the conflict, as well as the violations of international law. Through a normative juridical approach, this article examines the legal implications of veto power, particularly regarding its impact on the enforcement of international law.